2021
DOI: 10.1029/2020ja029071
|View full text |Cite
|
Sign up to set email alerts
|

Global Ionospheric Response to a Periodic Sequence of HSS/CIR Events During the 2007–2008 Solar Minimum

Abstract: The thermosphere-ionosphere system constitutes the upper-most layer of the Earth's atmosphere and is characterized by high variability and a strong dependence on external drivers. The two main categories of forcings are solar radiation and geomagnetic activity at high latitudes. Under normal conditions, solar radiation is the dominant source of energy and momentum, generating the standard structure, composition, and circulation of the thermosphere-ionosphere (Fuller-Rowell, 2014;Rishbeth & Garriott, 1969). Dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This is probably due to the recurrent interaction with the high-speed streams and the corotating interaction regions observed in 2008 and which are characterized by a more "ordered" structure of the interplanetary magnetic field. In a recent study, Munteanu et al (2019) showed that two systems of CIRs and HSS whose origin stayed stable on the Sun (same group of coronal holes) for several months in 2008, impacted the Earth, including for the time period investigated in this study (see, also, Negrea et al, 2021). While in 2007 the Earth was also impacted by HSS and CIRs their origin was more dynamic and their properties were therefore much more variable compared to 2008.…”
Section: Figurementioning
confidence: 63%
“…This is probably due to the recurrent interaction with the high-speed streams and the corotating interaction regions observed in 2008 and which are characterized by a more "ordered" structure of the interplanetary magnetic field. In a recent study, Munteanu et al (2019) showed that two systems of CIRs and HSS whose origin stayed stable on the Sun (same group of coronal holes) for several months in 2008, impacted the Earth, including for the time period investigated in this study (see, also, Negrea et al, 2021). While in 2007 the Earth was also impacted by HSS and CIRs their origin was more dynamic and their properties were therefore much more variable compared to 2008.…”
Section: Figurementioning
confidence: 63%